FROM SEXUAL ETHICS TO RELATIONAL ETHICS: ON THE DEBATE ON SEXUAL MORALITY IN THE CHURCH AND THEOLOGY - Konrad, Hilpert (Asian Horizons, 2015)
Sexual behaviour will become an important sector of morality only by the fact that it is enlivened through relations: sexual feeling and activity become moral or immoral only in so far as they have to do with respect for the autonomy of others, trust, understanding and reliance, responsibility for reproduction and good parenthood, justice in the distribution of burdens and duties of the partners.